Etnomatematika Pada Penentuan Hari Baik dalam Tradisi Membangun Rumah Jawa - Aris Aryanto (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Ethnomathematics is an intersection between culture and mathematics. The tradition of building a Javanese house has mathematical and cultural values that are very deep, such as determining good days and cultural procedures so that it becomes an interesting thing to study further. The purpose of this study is to determine the form of ethnomathematics in determining good days in the tradition of building a Javanese house and to find out the process of implementing the construction of a Javanese house. This research is an effort to present one form of local wisdom of the Javanese community which has a philosophical meaning behind Javanese ethnomathematics (petungan) carried out in the tradition of building a house. The form of this research is descriptive qualitative using an ethnographic approach. The research location is in Purworejo Regency, Central Java province. Data collection using direct observation techniques and direct interviews with research sources who know and understand more deeply about the tradition of building a Javanese house. The results showed that the form of ethnomathematics in the tradition of building Javanese houses is in the form of counting, measuring, and predicting activities. Then philosophically, the cultural value that emerges is that the tradition of building a house is an attempt to unite (Jw: nyawijikake) between the house and the person who built the house. That is, the house is considered to have a soul like a human being so that when it can be in harmony with the house, the occupants of the house will always feel peaceful and comfortable.